Implementasi Program Njuh Sekolah Maning Dalam Penanggulangan Anak Tidak Sekolah Di Kabupaten Pemalang Tahun 2023-2024 - Nur Roudloh Azzahra; Lusia Astrika (Journal of Politic and Government Studies, 2026)
This study analyzes in depth the implementation of the “Njuh Sekolah Maning” Program (NSM) in Pemalang Regency for the period 2023–2024 as a strategic effort to address Out-of-School Children (ATS), which was triggered by a drastic surge from 220 people (2020) to 8,356 people (2024) due to chronic structural poverty, limited geographical access in remote areas, the prevalence of early marriage, as well as low community awareness of the 12-year compulsory education; using a descriptive qualitative approach based on Merilee S. Grindle's (1980) policy implementation model that highlights the dimensions of content of policy and context of implementation, data were obtained through in-depth interviews with various stakeholders, field observations, as well as analysis of official documents such as Perbup No. 40/2021 and Dindikpora reports; the findings show that NSM has proven effective in reducing ATS through holistic interventions that include accurate data collection via SIPMB, door-to-door verification, provision of KIP-BOSDA-CSR assistance, intensive PKBM mentoring, vocational training based on local needs, as well as the addition of 18 new PKBM units, so that as of November 2025 it has successfully returned 13,551 children to formal/non-formal education with a peak achievement of 7,191 children in 2025; the success is supported by the strong political commitment of the regent, clear regulations, solid cross-sectoral synergy, as well as innovative local community participation, while the main inhibiting factors include extreme poverty, persistent child marriage practices, geographical access challenges, as well as budget and bureaucratic limitations; overall, NSM has become a national best practice for completing 12-year compulsory education in areas with heavy structural constraints and has the potential to drive an increase in Pemalang Regency's Human Development Index (HDI) to the high category in 2028–2030.